Where Emerging Adults in the United States Find Meaning in Life. Issue 1 (3rd April 2021) - Karayigit, Cebrail; Wood, Jamie
Abstract : We explored the most important sources of meaning among emerging adults and whether time spent on social media had an effect on life meaning dimensions. Results showed that the majority of emerging adults mentioned family and friends when asked in an open‐ended question about things that make their life meaningful.